The Role of Legal and Regulatory Frameworks for Sharia-Compliant Financing in Promoting Innovation and Quality Enhancement in Indonesia's Halal Industry - Riduan Mas’ud; Mohd Rizal Muwazir (UIN Sunan Gunung Djati, 2025)
Indonesia’s halal industry is experiencing rapid growth, driven by increasing consumer demand for products that comply with both sharia principles and global quality standards. This study examines the role of legal and regulatory frameworks governing sharia-compliant financing in supporting innovation and improving product quality within the halal sector. Using a qualitative research design with a descriptive-analytical approach, data were collected from 15 experts in Islamic finance, economic law, and halal business practices. The findings reveal that legal instruments—such as the Sharia Banking Law, regulations issued by the Financial Services Authority (OJK), and policies from the National Committee for Islamic Economy and Finance (KNEKS)—provide a legal foundation that facilitates ethical and inclusive access to capital. These frameworks contribute to the development of an innovative and competitive halal industry. However, challenges remain, including regulatory overlaps, weak enforcement mechanisms, and limited harmonization between central and regional regulations. The study concludes by recommending regulatory reforms and institutional strengthening to optimize the legal contribution to the sustainable growth of Indonesia’s halal industry.